2018
DOI: 10.1097/md.0000000000009509
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations and clinical significance of BRAF in malignant melanoma

Abstract: Malignant melanoma (MM) is a highly malignant melanocytic tumor, it occurs mostly in the skin, the mucous membrane close to the skin, but also in the tunicae rhagoides and the pia mater. The Uyghur is the largest ethnic group living in the Xinjiang Uyghur Autonomous Region of China, accounting for 46% of the total population of 20 million. Large-scale studies on MMs in Asian countries are limited. This study aimed to investigate BRAF mRNA expression and mutations in Chinese Uyghur patients with MMs and to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…When compared to other Asian countries, the BRAF V600 prevalence in this study is relatively high. This mutation is found in 11.9 to 41.8% of Asian melanoma cases in general [5,12,16,17]. The only two studies on Asian nodular melanoma cases reported the mutation prevalence at 29.4 and 50% [11,12].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When compared to other Asian countries, the BRAF V600 prevalence in this study is relatively high. This mutation is found in 11.9 to 41.8% of Asian melanoma cases in general [5,12,16,17]. The only two studies on Asian nodular melanoma cases reported the mutation prevalence at 29.4 and 50% [11,12].…”
Section: Discussionmentioning
confidence: 93%
“…Asian melanoma cases differ in characteristics from Caucasians, such as predominance of the acral lentiginous subtype and low BRAF mutation prevalence. Variations also exist within certain parts of Asia and even between different ethnicities [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This mutation is found in 11.9% to 41.8% of Asian melanoma cases in general (5,12,16,17). The only two studies on Asian nodular melanoma cases reported the mutation prevalence at 29.4% and 50% (11,12).…”
Section: Discussionmentioning
confidence: 94%
“…This mutation is found in 11.9-41.8% of Asian melanoma cases in general (5,11,15,16). The only two studies on Asian nodular melanoma cases reported the mutation prevalence at 29.4% and 50% (10,11).…”
Section: Discussionmentioning
confidence: 94%